Pembentukan Karakter Peserta Didik Berbasis Living Values Education Melalui Ekstrakurikuler Pramuka - Anam, Choirul; Maknuunah, Rismaa Jauharotul (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2023)
This study is motivated by the many phenomena that occur on the problem of social behavior deviations in the nation's children who cause a crisis of character. Character education is needed to minimize negative characters in children. LVE values that include the values of cooperation, freedom, happiness, honesty, humility, love, peace, respect, responsibility, simplicity, tolerance, and unity are the expectations of all people. One of the activities that implement character education is extracurricular scouting, which through its activities seeks to foster the character of students in order to have good character in them.This study uses a qualitative approach to the type of qualitative descriptive research with interviews, observations, and comments as data collection techniques. The subjects used were the principal, homeroom teacher, and scoutmaster.Based on the results of research that has been done, it can be concluded as follows: 1) the concept of character formation of students based on living values education through extracurricular scouting, namely, the necessary uniformity of steps in the implementation of extracurricular scouting through the Scout Movement program and standby gudep sdit Al-Kautsar Ngoro. 2) efforts in shaping the character of students through extracurricular scouting include routine exercises include the practice of the Scout movement honor code, learning by doing, team and group systems. In addition, the role model of scoutmaster in the implementation of extracurricular scouting is very influential in the formation of the value of the character of students. 3) supporting factors in the implementation of character building include scoutmaster, Guardian cooperation, adequate infrastructure. For an obstacle to the formation of character lies only in the division of time. Because there are various extracurricular activities in sdit Al-Kauthar school and the application of full day school makes all activities in learning dense. No action to overcome these barriers to character building can be implemented through learning and habit.